Synthesis of Fluorine Heterocyclic Nitrogen Systems Derived From Sulfa Drugs as PhotochemicalProbe Agents for Inhibition of Vitiligo Disease-Part II - Reda M. Abdel-Rahman; Mohammad Saleh I. T. Makki; Wafa A. Baker Bawazir (E-Journal of Chemistry)
Some more new bioactive fluorine heterocyclic systems containing sulfur and nitrogen as six-membered rings such as; N,Nʼ-disubstituted-thiobarbituric acid, 3-thioxo-1,2,4-triazino[5,6-b]indole, 3-sulfanilamido-1,2,4-triazino[5,6-b]indole and 2-trifluoromethyl-4-imino-6-(sulfamido)1,3,5-triazino [3,2-a]indole derivatives (2-13) have been synthetically derived from the interaction of sulfa drugs with fluorine organic compounds (aldehydes, ketones, anhydride) followed by ring closure reactions. Structures of the targets have been established from their elemental and spectral data. Compounds 3, 6, 10 and 13 could be used as photochemical probe agents in compared with nystatin and nalidixic acid for inhibition of vitiligo diseases.